Analysis of Depreciation of Archives in The Central Khazanah Archives - Deby Palista; Fransiska Timoria Samosir; Lailatus Sa’Diyah (Record and Library Journal, 2023)
Background of the study: The Bank Indonesia Representative Office creates and produces large numbers of archives every day. Bank Indonesia Representative Offices have their own system regarding records, namely MDBI (Bank Indonesia Document Management) which is supported by technology-based application tools, namely the BI-Records Management System (BI-RMS). This application is a system in the archive management process that is used regarding the form of activity of receiving or sending, filing, storing, using, maintaining, securing, and depreciating archives. Purpose: Knowing how to depreciate archives at Bank Indonesia Bengkulu Province and the obstacles in depreciating such archives. Method: This study used a qualitative case study method. Data collection was carried out through systematic observation and in-depth interviews with informants. Findings: The results of the study stated that there were several obstacles in shrinking archives. Transfer of archives is carried out based on the notification of the list of archives transferred to the BI-RMS system that appears when the archivist opens the system. In transferring archives, there are still several documents that do not have a code so that in determining KMJRBI, those who do not know the main tasks of the archive creation unit will likely be hampered in determining the archive classification code so that the archive depreciation process becomes less effective. Conclusion: The difficulty of determining the JRA for certain documents lies in the fact that JR of several different documents takes considerable for archivists to determine the JRA. In response to these obstacles, the Bengkulu Province Bank Indonesia Representative Office can conduct training to improve archivist competence in managing records, especially in the depreciation section.